Respuesta :

Space

Answer:

y - 6 = -7(x + 9)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

Slope Formula: [tex]m=\frac{y_2-y_1}{x_2-x_1}[/tex]

Point-Slope Form: y - y₁ = m(x - x₁)  

  • x₁ - x coordinate
  • y₁ - y coordinate
  • m - slope

Step-by-step explanation:

Step 1: Define

Point (-9, 6)

Point (-7, -8)

Step 2: Find slope m

Simply plug in the 2 coordinates into the slope formula to find slope m

  1. Substitute [SF]:                    [tex]m=\frac{-8-6}{-7+9}[/tex]
  2. Subtract/Add:                      [tex]m=\frac{-14}{2}[/tex]
  3. Divide:                                  [tex]m=-7[/tex]

Step 3: Find Equation

Plug in variables into the general form.

y - 6 = -7(x + 9)

ACCESS MORE